Safety of Tumor Treating Fields (TTFields) therapy in pediatric patients with malignant brain tumors: Post-marketing surveillance data - Goldman, Stewart; Margol, Ashley; Hwang, Eugene I.; Tanaka, Kazuhiro; Suchorska, Bogdana; Crawford, John R.; Kesari, Santosh (Frontiers in Oncology, 2022)
There is an unmet need to develop effective and tolerable treatments for pediatric patients with malignant central nervous system tumors. This is especially essential for pediatric patients with aggressive brain tumors such as high-grade gliomas which have a typical survival rate of under 2 years. Tumor Treating Fields (TTFields) are locoregional, noninvasive electric fields that produce an antimitotic effect on cancerous cells when applied to the skin via arrays. TTFields therapy (200 kHz) is currently approved in adult patients with newly diagnosed glioblastoma (GBM), with temozolomide, and recurrent GBM as monotherapy. Positive preclinical and clinical data have encouraged off-label use of TTFields therapy in pediatric patients with brain tumors, and this study aims to explore the safety of TTFields therapy in pediatric patients (0–18 years of age) based on data from an unsolicited post-marketing surveillance safety database. The real-world data reported here demonstrate that TTFields therapy has a favorable safety profile for pediatric patients with brain tumors, with no new safety signals observed. Findings from this study warrant further research into the efficacy of TTFields therapy, as well as its potential impact on the quality of life in pediatric patients.